Knowledge, Attitudes, and Practices Related to Heat Stress in the Climate of Koper and Ljubljana (Slovenia) - Gorenc, Tomaž (Geographica Pannonica, 2025)
This study examines the knowledge, attitudes, and practices related to heat stress among residents of two distinct urban neighbourhoods in Slovenia with different climate types: Olmo, Koper, and Zupančičeva jama, Ljubljana. The study explored the interplay of socio-economic indicators, demographic characteristics, and health status with heat stress KAP. While both locations demonstrated comparable levels of knowledge regarding heat stress, residents of Olmo exhibited significantly more positive attitudes towards adopting preventive measures and reported engaging in such behaviours more frequently. The findings suggest that targeted interventions must consider not only knowledge dissemination but also the unique characteristics of each community, including their specific climate, socio-economic profile, and cultural norms, to effectively enhance community resilience to the adverse impacts of heat stress.
Keywords: KAP; climate adaptation; heat stress; climate change; socio-economic impacts; human perception of weather and climate; Slovenia